Public Willingness to Pay for and Participate in Sanitation Infrastructure Improvement in Western China's Rural Areas - Simei Wu; Simei Wu; Simei Wu; Yang Zhang; Bao-Jie He; Bao-Jie He (Frontiers Media S.A., 2022)
The suitability and feasibility of public-private partnership (PPP) patterns in a rural context have not been well-documented and understood. To address this research gap and practical plight, this study aims to analyze the rural resident's willingness to pay for and participate in the improvement of rural sanitation facilities, and further explore the drivers and barriers affecting their decisions. This study was performed in rural areas of three western provinces, including Shaanxi, Ningxia, and Inner Mongolia, of western China's rural areas by conducting a survey on 1,248 rural residents. In Inner Mongolia, the proportion of respondents who were willing to pay was highest, while the proportion of respondents who may provide labor was lowest among the three provinces. Respondents from Ningxia had the least willing to pay, and respondents from Shaanxi had the highest willingness to participate. Overall, respondents' rural (living) duration time, personal interest in local government notice, and the latest time when the sanitation facilities were improved could significantly affect their willingness. In Inner Mongolia, occupation and water availability could significantly influence respondents' willingness, and both gender and health conditions had significant impacts. In Ningxia, respondents' personal interest in local government notice had a notable impact on willingness, and low-income respondents showed a more notable willingness to pay and participate. In Shaanxi, occupation and water availability could significantly influence respondents' willingness. Respondents' personal interest in local government notice had a notable impact on their willingness. This study is of significant importance to understand rural resident's participation in sanitation infrastructure improvement to support relevant PPP projects, and is important to solve poverty-caused dilemmas.